Perioperative liberal versus restrictive fluid strategies and postoperative outcomes: a systematic review and metanalysis on randomised-controlled trials in major abdominal elective surgery - Antonio Messina; Chiara Robba; Lorenzo Calabrò; Daniel Zambelli; Francesca Iannuzzi; Edoardo Molinari; Silvia Scarano; Denise Battaglini; Marta Baggiani; Giacomo De Mattei; Laura Saderi; Giovanni Sotgiu; et al. (Critical Care, 2021)
Abstract Background Postoperative complications impact on early and long-term patients’ outcome. Appropriate perioperative fluid management is pivotal in this context; however, the most effective perioperative fluid management is still unclear. The enhanced recovery after surgery pathways recommend a perioperative zero-balance, whereas recent findings suggest a more liberal approach could be beneficial. We conducted this trial to address the impact of restrictive vs. liberal fluid approaches on overall postoperative complications and mortality. Methods Systematic review and meta-analysis, including randomised controlled trials (RCTs). We performed a systematic literature search using MEDLINE (via Ovid), EMBASE (via Ovid) and the Cochrane Controlled Clinical trials register databases, published from 1 January 2000 to 31 December 2019. We included RCTs enrolling adult patients undergoing elective abdominal surgery and comparing the use of restrictive/liberal approaches enrolling at least 15 patients in each subgroup. Studies involving cardiac, non-elective surgery, paediatric or obstetric surgeries were excluded. Results After full-text examination, the metanalysis finally included 18 studies and 5567 patients randomised to restrictive (2786 patients; 50.0%) or liberal approaches (2780 patients; 50.0%). We found no difference in the occurrence of severe postoperative complications between restrictive and liberal subgroups [risk difference (95% CI) = 0.009 (− 0.02; 0.04); p value = 0.62; I 2 (95% CI) = 38.6% (0–66.9%)]. This result was confirmed also in the subgroup of five studies having a low overall risk of bias. The liberal approach was associated with lower overall renal major events, as compared to the restrictive [risk difference (95% CI) = 0.06 (0.02–0.09); p value  = 0.001]. We found no difference in either early (p value  = 0.33) or late (p value  = 0.22) postoperative mortality between restrictive and liberal subgroups Conclusions In major abdominal elective surgery perioperative, the choice between liberal or restrictive approach did not affect overall major postoperative complications or mortality. In a subgroup analysis, a liberal as compared to a restrictive perioperative fluid policy was associated with lower overall complication renal major events, as compared to the restrictive. Trial Registration CRD42020218059; Registration: February 2020, https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=218059 .